Universities and innovation in space - Michael Fritsch; Viktor Slavtchev (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
We investigate the role of universities as a knowledge source for regional innovation processes. The contribution of universities is tested on the level of German NUTS-3 regions (Kreise) by using a variety of indicators. We find that the intensity and quality of the research conducted by the universities have a significant effect on regional innovative output while pure size is unimportant. Therefore, a policy that wants to promote regional innovation processes by building up universities should place substantial emphasis on the intensity and quality of the research conducted there.
Keywords: O31; O18; R12; 330; Universities; innovation; knowledge; spillovers; patents; regional Analysis; Hochschule; Wissenstransfer; Innovationsdiffusion; Regionalökonomik; Schätzung; Deutschland